Implementación de un sistema de monitoreo para la incubación de aves vía página web con alertas por tweets mediante Arduino 111111 - José David Esquicha Tejada (2017)
This article discusses the implementation of a remote monitoring system for incubating birds in real time to measure temperature, of each egg incubated using Arduino board. The project is based on send alerts via Twitter tweets service when the temperature is high or low by integrating Ethernet Arduino Shield, when the temperature is high begins to operate the cooler (fan) to reduce heat inside the incubator and when it is cold leaves to operate the cooler, additionally, the proposal records all movements within the incubator through motion detection sensor (PIR), also it has added two relays (relay) controlling the ignition of a red light when the high temperature and a yellow light when the temperature is low useful to warn when any change occurs within the incubator. Finally, the proposal includes a Web page that is mounted on the Arduino through the Shield Ethernet, which can display the sensors (PIR, temperature and humidity) and actuators (focus and LED) is web can be viewed on any device (desktop PC, Laptop, Smartphone or Tablet).